Our cultural collections : a guide to the treasures held by South Australia's collecting institutions. - Arts South Australia (Adelaide, SA : Arts SA, 2014)
Summarises the collections of the Art Gallery of South Australia, the South Australian Museum, the State Library of South Australia, Carrick Hill, and History SA.
Our cultural collections, a guide to the treasures held by South Australia's collecting institutions -- South Australia's cultural institutions -- Art Gallery of South Australia -- South Australian Museum -- State Library of South Australia -- Carrick Hill -- History SA -- Artlab Australia.
Cover title.
Keywords: Art Gallery of South Australia; South Australian Museum; State Library of South Australia; Carrick Hill Foundation; History SA; Artlab Australia; Art museums -- South Australia -- Adelaide; Historical museums -- South Australia -- Adelaide; Australian